Dynamics of emergency management in the Gangwon province, Korea. (2nd January 2016) - Ha, Kyoo-Man
ABSTRACT: While fully utilizing the principles of international emergency management, the objective of this article was to evaluate the present local emergency management of the Gangwon province in relation to its future requirements, and ultimately, to arrive at the most effective emergency-management plan. In doing so, both reality-oriented and risk-oriented approaches were compared via four key players or stakeholders, namely the local governments, military forces, local industries, and semi-volunteers and households. Literature review and interviews with national experts were utilized as the methodology for this study. The contribution of this paper is valuable, because the case of the Gangwon province was examined, for the first time, using international criteria. The key finding is that for best practices, the Gangwon province has to change its reality-oriented approach to a risk-oriented approach. Furthermore, the evaluation of the Gangwon province's policies following international emergency-management examples may result to improvements on the non-linear dynamics of local emergency management and facilitate transformation toward a risk-oriented approach in neighboring countries.